EVALUASI PENYEBAB HASIL INVALID PADA PEMERIKSAAN RT-PCR PASIEN COVID-19 - Christina destri Wiwis Wijayanti; Sulistyowatiningsih Sulistyowatiningsih; Halik Wijaya (Jurnal SainHealth, 2022)
The COVID-19 pandemic has occurred in Indonesia since March 2020. An increase in cases requires the involvement of various medical elements from the beginning of the patient's condition to the diagnosis decision. Preparation of pre-analysis, analysis, to good post-analysis in the laboratory greatly supports the results of the diagnosis needed. The purpose of this study was to find out various factors that influence invalid results in a real-time examination – polymerase chain reaction (RT-PCR) in patients at Dr. Wahidin Sudirohusodo Mojokerto general hospital. Data collection from the hospital's biomolecular laboratory in a cross-sectional descriptive observational manner was taken from September to November 2020. A total of 40 data processed with descriptive statistics percentage showed a tendency to invalidity results by 30%. Pre-analytic errors play a big role in the RT-PCR method inspection process. Sample misidentification, poor sample quality, non-standard sample transportation conditions,  and sample storage are some of the things that support the invalidity of the results of the COVID-19 RT-PCR examination method. Evaluation during the work process at various stages as well as the use of controls can minimize laboratory results that are not appropriate. Keywords : COVID-19, RT-PCR, Invalid